Revising secularization theory’s paradigmatic core: David Martin on general processes, basic patterns and causal mechanisms of differentiation between religion and politics 1 - Koenig, Matthias (David Martin and the sociology of religion, 2018)
While the paradigmatic core of secularization theory, namely the assumption that modernity entailed the functional differentiation of religion from other
Gesehen am 28.04.2021